The Distinct Seasonality of Early Modern Casual Labor and the Short Durations of Individual Working Years: Sweden 1500–1800 - Gary, Kathryn E. (International review of social history, 2025)
This article makes use of nearly 25,000 observations representing over 95,000 paid workdays across over 300 years to investigate individual work patterns, work availability, and the changes in work seasonality over time. This sample is comprised of workers in the construction industry, and includes unskilled men and women as well as skilled building craftsmen – the industry that is often used to estimate comparative real wages through early modern Europe. Data come predominantly from Scania, the southernmost region in modern day Sweden, and especially from Malmö, the largest town in the region. Findings indicate that workers probably do not engage in paid labour on a purely labour-supply-based schedule, but are strongly impacted by the demand for construction labour, which was highly seasonal and impacted by local labour institutions. Seasonality was stronger further back in the past, indicating that finding long-term work may have been more difficult in earlier periods. A typical work year could probably not have been longer than 150 days, and would be made up of shorter work spells at several different sites. This is not enough work to meet standard assumptions of 250 days, or enough work for an unskilled man to support his family at a respectable level. Individual workers rarely worked more than a handful of days in a year on a construction site, even when labour demand was high, indicating that they did not maximize their income from waged labour.